Quasi-nonlinear distortion of signals in closed space for an unsteady state - CZARNECKI, Stefan; WYGAŃSKI, Władysław (Archives of Acoustics, 1982)
This paper discusses the possibility of signal distortions occurring in closed space for the rise and decay of signals. A theoretical analysis is conducted for a simplified case in which the character of phenomena is analyzed in relation to the value of the ratio of the time delay between successive signals and their period.The later part of this paper gives experimental results which confirm the possibility of distortions occurring in real conditions. It also discusses the possibility of the occurrence of phase, frequency and amplitude modulation and gives examples of signal shape distortion in its rising, obtained in two concert halls in the Academy of Music, Warsaw.A subjective analysis was performed of the audibility of distortions in simulated signals which were programmed with a regular kind of distortion. The results of distortion audibility in % and the subjective analysis of the audibility of distortions in real conditions have shown that these distortions can be perceived with their short duration of the order of several or a dozen or so milliseconds.